Sleep and Cognition in Preschool Years: Specific Links to Executive Functioning. Issue 5 (24th February 2013) - Bernier, Annie; Beauchamp, Miriam H.; Bouvette‐Turcot, Andrée‐Anne; Carlson, Stephanie M.; Carrier, Julie
Abstract : This study investigated the prospective links between sleep in infancy and preschoolers' cognitive performance. Mothers of 65 infants completed a sleep diary when infants were aged 1 year, and children completed two subscales of the Wechsler Preschool and Primary Scale of Intelligence at 4 years, indexing general cognitive ability and complex executive functioning. Consistent with hypotheses, children getting higher proportions of their sleep at night as infants were found to perform better on executive functions, but did not show better general cognition. Relations held after controlling for family socioeconomic status and prior cognitive functioning. These findings suggest that the special importance of sleep for higher order cognition, documented among adults, may appear very early in life.